Browning of clarified lemon juices treated at high temperatures - Ibarz-Martínez, Raquel (2010)
In this work a study of effect of high temperature treatments (70, 80, 90 and 95oC) on color evolution in clarified lemon juices (10, 20, 35, 50 and 64.6oBrix) has been carried out. The evolution of the color with the treatment time has been continued measuring the absorbance at 420 nm (A420) and the parameters CIELab (L*, a* and b*) and color increment E *. The increase of A420 and of the decrease of the brightness L * with the time of treatment it has been observed that they are fitted to a zero order kinetic, what has allowed to obtain the corresponding ones constant kinetic of color deterioration. The evolution of E* has been described by a kinetic model in two steps. The effect of the temperature on these kinetic constants can be quantified by means of the Arrhenius equation, what allows obtaining the corresponding values of activation energy. For the A420 and L* activation energy values tends to decrease with the increase of concentration while for E* variation hardly exists. For the treatments to a certain temperature, the effect of the soluble solids content on the kinetic constants can be described by means of a model exponential type equation.